Chest CT findings of pleural tuberculosis: differential diagnosis of pleural tuberculosis and malignant pleural dissemination. (November 2014) - Kim, Jin Sil; Shim, Sung Shine; Kim, Yookyung; Ryu, Yon Ju; Lee, Jin Hwa
Background: The imaging features of pleural tuberculosis (PTB) can be similar to those of malignant pleural dissemination (MPD) with several case reports of CT findings in atypical presentations of PTB. Purpose: To describe the computed tomography (CT) features of PTB by comparing these imaging findings with those of MPD and to use the results to differentiate between the two diseases. Material and Methods: The study included 135 patients with PTB and 69 with MPD. The CT images were assessed in terms of the presence, extent, and contour of pleural thickening. Pleural nodules were analyzed in terms of number, size, and location. The CT findings of PTB and MPD were compared. Results: The CT findings of PTB included circumferential pleural thickening (32.6%), mediastinal pleural involvement (31.9%), nodular thickening (8.9%), and pleural thickening >1 cm (2.2%). The CT features of MPD included nodular pleural thickening (56.5%), mediastinal pleural involvement (40.6%), circumferential thickening (23.2%), and pleural thickening >1 cm (7.2%). Comparing PTB and MPD, nodular pleural thickening was observed more frequently with MPD than PTB ( P  <0.001). Conclusion: Nodular pleural thickening is observed in 8.9% of the patients with PTB on chest CT. Comparing PTB and MPD, nodular pleural thickening was the only finding significantly associated with MPD, particularly with nodules >10 mm.